Surgical Prevention of Thromboembolic Complications in Transfascial Thrombosis - Popovich, Yaroslav M.; Korsak, Vyacheslav V.; Boldizhar, Patricia O.; Laver, Orest P. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To evaluate the effectiveness of surgical methods of prevention of venous thromboembolic complications in transfascial thrombosis of the lower extremities. Materials and methods. The paper analyzes the results of examination and surgical or conservative treatment of 417 patients with transfascial thrombosis treated at the Vascular Surgery Department of the Zakarpattia Regional Clinical Hospital named after A. Novak from 1995 to March 2020 and at the Surgical Department of the Central City Clinical Hospital of Uzhhorod from September 2020 to September 2022. The main (I) group consisted of 349 (83.7%) patients who were operated for transfascial thrombosis. The control (II) group consisted of 68 (16.3%) patients with transfascial thrombosis who received conservative treatment. Results. In case of acute varicothrombophlebitis complicated by transfascial thrombosis, the scope of surgery should be expanded in order to surgically prevent thromboembolism of the pulmonary artery. All the patients with transfascial thrombosis were treated as for deep vein thrombosis. The approach to the removal of the small saphenous vein should be differentiated depending on the extent of thrombotic occlusion and the confluence of the sural veins. Surgical treatment of patients with transfascial thrombosis made it possible to prevent recurrence of the thrombotic process in the superficial and deep veins of the lower extremities, thromboembolism of the pulmonary artery, while with conservative treatment their frequency was 5.1%, 3.4% and 3.4%, respectively. Active surgical tactics in patients of the I group made it possible to reduce the frequency of manifestations of decompensated chronic venous insufficiency from 27.1% to 7.0%, and manifestations of postthrombotic syndrome in the deep veins of the lower extremities from 100% to 3.7%. Conclusions. Implementation of operative treatment of acute varicothrombophlebitis complicated by transfascial thrombosis allows to effectively prevent venous thromboembolic complications, eliminate manifestations of chronic venous insufficiency and prevent the development of post-thrombotic changes in superficial and deep veins.